Prognostic significance of thrombus burden on short- and long-term clinical outcomes in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention. Issue 7 (9th August 2022) - Köktürk, Uğur; Somuncu, Mustafa Umut; Uygur, Begüm; Akgül, Özgür; Püşüroğlu, Hamdi
Abstract : Objective: Large thrombus burden (LTB) observed during ST-segment elevation myocardial infarction (STEMI) may end up with worse clinical outcomes. The relationship between LTB and long-term mortality and major adverse cardiac events (MACE) in STEMI patients undergoing percutaneous coronary intervention (PCI) is unclear. In this study, we aimed to investigate the relationship of LTB with short- and long-term mortality and MACE in STEMI patients undergoing PCI. Methods: Thrombus burden (TB) was evaluated in STEMI patients who underwent PCI between December 2010 and April 2012. After infarct-related arterial flow was restored, TB was reclassified. LTB was defined as thrombus with the largest dimension of at least two vessel diameters. Patients were evaluated for 1-month, 1-year, and 10-year follow-ups in terms of MACE and mortality. Results: Four hundred ninety-nine patients with clinical information and TB classification were analyzed. Three hundred sixty-six patients (73.3%) were in the small TB (STB) group, and 133 patients (26.7%) were in the LTB group. No-reflow (10.6% vs. 5.2%; P = 0.033) and stent thrombosis (7.5% vs. 3.3%; P = 0.042) were observed at a higher rate in the LTB group compared with the STB group. Thirty-day mortality (9.8% vs. 3.8%; P = 0.009) and MACE (16.5% vs. 9.6%; P = 0.030) were higher in the LTB group than in the STB group. Although 10-year MACE (56.4% vs. 46.2%; P = 0.044) was observed higher in the LTB group, no significant difference was observed between the two groups in terms of 10-year mortality (35.3% vs. 32.8%; P = 0.589). LTB was found to be an independent predictor for 10-year MACE (OR, 1.62; 95% CI, 1.01–2.61; P = 0.045). Conclusion: LTB was associated with short- and long-term clinical events in STEMI patients undergoing PCI, but the mortality effect disappeared at the end of 1 year. Nevertheless, hospitalizations due to heart failure became significant in 10-year follow-up.